Incorporation of pink pepper residue extract into chitosan film combined with a modified atmosphere packaging: Effects on the shelf life of salmon fillets - Merlo, Thais Cardoso (2019)
Authors acknowledge the São Paulo Research Foundation (FAPESP, Brazil) for financing the project 2016/10888-7. Thais C. Merlo received the Masters Scholarship from the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) – Finance Code 001. Authors thank Sealed Air for donating the modified atmosphere packaging for the project and Marcomar importer and distributor of fish for the donation of the raw material. Erick Saldaña received the Ph.D Scholarship from the Peruvian “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica - CONCYTEC” (CIENCIACTIVA programme, contract agreement No. 104-2016-FONDECYT).